Prevalence of Myocardial Fibrosis in Intensive Endurance Training Athletes: A Systematic Review and Meta-Analysis - Zhang, Cheng-Duo; Xu, Shun-Lin; Wang, Xin-Yu; Tao, Li-Yuan; Zhao, Wei; Gao, Wei (Frontiers in Cardiovascular Medicine, 2020)
Objective: To review the published literature reporting on the incidence of myocardial fibrosis (MF) in high-intensity endurance athletes measured by late gadolinium enhancement (LGE) with cardiac magnetic resonance imaging (CMR). Methods: Five databases (PubMed, Cochrane Controlled Trials Register, EMBASE, Web of Science, and SPORTDiscus) were searched to obtain case cohort studies published before November 10, 2019. From 96 abstracts or reports extracted, 18 full-text articles were reviewed. The incidence of LGE was reported as outcome measures. Subgroup analysis was performed by age (under or above 50 years). Pooled estimates were obtained using a fixed-effects model. Results: After a full-text assessment, 12 studies involving 1359 participants were included for analysis. Among them, 163/772 participants in the endurance athletes group showed LGE positive, compared with 19/587 participants in the comparison group. The results of the meta-analysis suggested that the prevalence of LGE was higher in the athletes group with long-term endurance exercise (OR 7.20; 95%CI: 4.51-11.49). In addition, the same conclusion was drawn after the stratification of age. Conclusions: The available evidence demonstrates that high-intensity endurance athletes is associated with an increased incidence of LGE positive.